Spatio-Temporal Evolution and Influencing Factors of Open Economy Development in the Yangtze River Delta Area - Debin Ma; Jie Zhang; Ziyi Wang; Dongqi Sun (Land, 2022)
Since economic globalization is unstable, it is difficult for the traditional open economic development model to meet the requirements of China’s development, and there is an urgent need for new ideas and models to be reoriented. Based on the analysis of the development mechanism of China’s open economy at this stage, we used the entropy method, Theil coefficient, Gini coefficient, and spatial Durbin model (SDM) to analyze the spatio-temporal pattern and influencing factors of the high-quality development level of the open economy in the Yangtze River Delta Area (YRDA). The results indicated that during the study period, the development level and development difference of open economy were on the rise, and the spatial difference in different regions was significant. The development of open economy was affected by many factors, and there was a spatial spillover effect. Based on the existing problems, at the stage of high-quality economic development, the YDRA should seize the opportunities brought by the new development pattern, improve government services, optimize innovation drive, and promote the development of open economy to a higher level. We believe that the results of this study can also provide relevant experience for the development of open economy in other regions of China.